Implications of The Rules of Al-Masyaqqah Tajlibu At-Taisir in The Contract of Greetings - Masithoh Masithoh (International Journal of Social Service and Research, 2023)
This research discusses buying and selling greetings in the context of online trading activities in Indonesia. Buying and selling greetings is a sale and purchase contract allowed in Islam, where the buyer orders goods with agreed criteria and pays in cash when the contract is executed. In buying and selling greetings, there is no element of deception or gharar (uncertainty) involved. This research uses a phenomenological approach with qualitative descriptive research methods of literature. The data used is obtained from books, journals, and texts related to buying and selling online in the marketplace. The article also discusses the contract of salam in a sharia perspective such as the rule of al-Masyaqqah Tajlibu At-Taisir, namely difficulties will encourage convenience, such as transactions using online applications, where salam is the sale and purchase of goods mentioned in nature in dependents with payments made right away. The greeting agreement may be deferred until a certain time and payment can be made in cash. In the greeting contract, there is a delivery of goods at a later date with the price, specifications, quantity, quality, date, and place of delivery that has been agreed before.